Traditional Game of Tapak Gunung as Thematic Teaching Materials for Class II Elementary School (Musamus Journal of Primary Education)
This research aims to develop a Student Activity Sheet (LKPD) based on traditional mountain footprint games for grade II students and evaluate the level of practicality in learning. The method used is Research and Development (R&D) with the ADDIE model which involves five stages, namely analysis, design, development, implementation, and evaluation. Data was collected through instruments in the form of questionnaires that involved validation by media experts, material experts, lesson plan experts, and practicality tests by users. The product trial was carried out on 50 grade II students from three schools in Kapanewon Pengasih, namely SD Negeri Kepek, SD Negeri Margosari, and SD Negeri 2 Karangsari. The results of the study show that the LKPD developed has a high level of validity, with a media validation percentage of 78% (valid category), material validation of 80% (valid category), and RPP validation of 85% (very valid category). In addition, the results of the practicality test obtained a score of 90.24% (very practical category), while the level of learning completeness reached 88% (effective category). Thus, the LKPD based on the mountain footprint game is declared valid, practical, and effective to support thematic learning in grade II of elementary school.